2018
DOI: 10.26877/eternal.v9i2.2976
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Strategic Reading in EFL Reading Classroom

Abstract: This study aims to find out whether the collaborative strategic reading can significantly improve the students` reading comprehension achievement and what the students` perceptions on the use of collaborative strategic reading in EFL reading classroom are. The result showed that collaborative strategic reading can significantly improve the students reading achievement. The paired sample test showed the comparison of pretest and posttest score displayed the difference between scores. The mean difference was 15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Regarding language development, other relevant studies also documented that students involved in DST instruction felt their English skills improved, especially for vocabulary enhancement and listening skills (e.g., Tabieh et al, 2020;Gaya, 2018). The improvement of students learning motivations also resonated with the previous study (i.e., Aziz & Husnawadi, 2020;Anggeraini, 2017). Aziz and Husnawadi (2020) revealed that students got highly motivated to study during the second task.…”
Section: Learning Motivationsupporting
confidence: 56%
See 2 more Smart Citations
“…Regarding language development, other relevant studies also documented that students involved in DST instruction felt their English skills improved, especially for vocabulary enhancement and listening skills (e.g., Tabieh et al, 2020;Gaya, 2018). The improvement of students learning motivations also resonated with the previous study (i.e., Aziz & Husnawadi, 2020;Anggeraini, 2017). Aziz and Husnawadi (2020) revealed that students got highly motivated to study during the second task.…”
Section: Learning Motivationsupporting
confidence: 56%
“…Furthermore, in learning the reading subject, DST is performed to help students improve their academic performance. (Anggeraini, 2017) experimental research aimed to determine the students' primary conditions on reading short story texts before using digital storytelling than how DST was developed for reading a short story to students, and how effective the developed digital storytelling used for teaching reading is. The findings of this study revealed that digital storytelling media meet the needs of students who have a variety of criteria, including the interest to learn vocabulary, reading dramatic and romantic stories by reading short stories.…”
Section: Previous Studies Of Using Dstmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaborative Strategic Reading (CSR) fits the problems in learning to read narrative texts because it can improve students' motivation to study, comprehension, imagination, critical thinking, group work, and social skills. Collaborative Strategic Reading (CSR) helps students to improve reading comprehension and increase conceptual learning in ways that maximize students' participation (Anggeraini et al, 2018). In addition, CSR is a process of combining reading comprehension with strategic instruction and cooperative learning and is applied as a set of reading comprehension strategies (Chuong & Huong, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of multifunctional and low-cost digital devices, such as smartphones that capture high-quality video, DST has become increasingly popular. Stories are usually 2 to 10 minutes in length [5], and told through a combination of sound, stills, animation, music, etc. [6].…”
Section: Introductionmentioning
confidence: 99%